Pembelajaran Matematika Dengan Remedial Melalui Belajar Kooperatif Tipe Student Teams-Achievement Division (STAD) Terhadap Hasil Belajar Siswa - Susilo, Ndari; Muslimin, Muslimin; Nery, Rieno Septra (Universitas Muhammadiyah Palembang, 2019)
The purpose of this research is to find out whether there is an influence of learning mathematics with remedial through cooperative learning type Student Teams-Achievement Division (STAD) on student learning outcomes in Palembang State High School 2. This type of research is experimental research. From the collected data, students' learning outcomes with remedial learning through cooperative learning type Student Teams-Achievement Division (STAD) the average value is 78,52 and standard deviation (S1) = 9,19 with the number of students 31 people and student learning outcomes without remedial and without going through cooperative learning type Student Teams-Achievement Division (STAD) the average value is 66,00 and standard deviation (S2) = 10,92 with 31 students. Based on the hypothesis testing criteria, the price of tcount = 4.88 and ttabel = 2.00. This means that tcount is in the rejection area H0. Thus, the hypothesis stating that there is an influence of the use of STAD type cooperative learning models on student learning outcomes with remedial mathematics in linear program material in the experimental class is accepted.